Continued-fraction formalism applied to the spin-1/2 XYZ model - Sardella, Edson [UNESP] (American Physical Society (APS), 1991)
In this paper, we evaluate the correlation functions of the spin-1/2 XYZ model for some particular cases by using the Mori continued-fraction formalism. The results are exactly the same as those well-known ones. This removes any doubt about the convergence of the continued fraction recently raised by some authors. © 1991 The American Physical Society.